Primary Biliary Cirrhosis and Hemolytic Anemia Confusing Serum Bilirubin Levels - M Brackstone; Cameron N Ghent (Canadian Journal of Gastroenterology)
Hemolysis is observed in more than 50% of patients with cirrhosis. However, there has been little documention of the association of primary biliary cirrhosis with autoimmune hemolytic anemia. Two cases, found within a single practice, of primary biliary cirrhosis coexisting with autoimmune hemolysis and a third case coexisting with hereditary spherocytosis are presented. Anemia in such patients is commonly attributed to chronic disease, and hyperbilirubinemia is attributed to primary biliary cirrhosis. These patients were considered for liver transplantation until the diagnosis of a comorbid hemolytic process was established. This association may be more prevalent than previously recognized. A diagnosis of comorbid hemolysis must always be considered in context with anemia and serum bilirubin levels that rise out of proportion to the severity of the primary biliary cirrhosis.